Top Notch : - Saslow, Joan (Pearson, 2006)
Top Notch, a dynamic 6 - level course for international communication, sets a new standard, using the natural language that people really speak. With a rock - soil learner - centered appoach, Top Notch provides students an opportunity to confirm their own progress at the end of every easy - to - teach two - page lesson.